Contained within history. Issue 1 (1st January 2018) - Robb, John
ABSTRACT: What a macro-history of containers look like? Containers are not really a bounded category of thing; they are a relational technology which transforms things into assemblages. Their history is thus that of an unbounded history of relations between things, rather than a bounded history of discrete objects.